Preliminary Overview of Three Purpose-Built Capital Spatial Plans Related to Indonesian Capital Relocation Plan - Hitapriya Suprayitno; Abd Muluk bin Abd Manan; Tri Mulyani Sunarharum (Journal of Infrastructure & Facility Asset Management, 2020)
Indonesia has a program to relocate its capital from Jakarta to East Kalimantan Province. This is a big and complex problem and is very interesting for Infrastructure & Facility Asset Management. Develop reflection on the case is very good to enrich and to develop IFAM knowledge and science. The first step has been done by developing an overview of several capital relocation cases. This research, the second step, is designated to make observations on the spatial plan of three good capitals. Visiting experience of the authors, enriched by literature study has been conducted. The reseach has main conclusions. It is better to develop a new city on an empty inhabited area. The symbolic aspect of the city is very important. A good plan, development, and control must be applied. The city must be green and intelligent. The capital must be divided into core areas for accomodating government offices and the peripheral area for accomodating residential areas and recreational areas. Well designed vast enough open space and several green parks are needed. The whole city must be furnished with good urban public transport. A good domestic and international accessibility is capital.